Psychometric analysis of a purposeful delay scale in Peruvian college students - Dominguez-Lara, Sergio; Rodríguez- Sullca, Fiorela; Moreta-Herrera, Rodrigo (Instituto de Investigaciones Psicológicas, 2022)
The objective of this research is to perform a psychometric analysis of the New Active Procrastination Scale (NAPS). The instrumental investigation included the participation of 472 students (66.1% women; Mage = 20,138) from three professional careers at a private university in Lima. The results show that the four-dimensional structure (preference for pressure, intentional decision, ability to meet deadlines, and outcome satisfaction) presents favorable evidence (proper adjustment indexes, items with moderate factorial loads and factorial simplicity). Furthermore, the bivariate association between the dimensions of the construct and the measures of academic burnout, depression and anxiety was significant (r> .20), although a subsequent hierarchical regression indicated that it only provides a significant variation to academic burnout (ΔR2> .10). Finally, the reliability coefficients were acceptable (> .70). In conclusion, the NAPS have favorable psychometric evidence in Peruvian college students.